Comparison of post-dural puncture headache- incidence and severity in obstetric patients after spinal anesthesia for caesarean section with 25G and 27G quincke needle - Syed, Sumaya; Qayoom, Nargis; Naaz, Shazia; Mushtaq, Khalida; Mir, Aabid Hussain; Bijli, Akram Hussain; Ali, Zulfiqar (International Journal of Research in Medical Sciences, 2017)
Background: The use of neuraxial anesthesia for caesarean section has dramatically increased in last 2 decades because it is easier to perform, safe to the mother and the fetus, and has a high degree of success rate. However, post-dural puncture headache is a well-known complication of spinal anesthesia. It is a common and incapacitating compliation following dura-arachnoid puncture and results in increased morbidity, prolonged hospital stay, increased cost, and patient dissatisfaction. Methods: It was a double-blinded comparative study conducted on 75 consecutive pregnant patients meeting the inclusion criteria of the study. Patient and anesthesiologist involved in collection of data were blinded to the gauge of the needle used. Standard anesthesia protocol was followed in all the patients and spinal anesthesia performed using 25G Quincke needle in 38 patients and 27G Quincke needle in 37 patients. Results: we included 75 consecutive patients in the age group 20-35 years in the study. Overall incidence of PDPH was 14.67% (11/75) in present study. 23.68% (9/38) and 5.4% (2/37) patients who received spinal anesthesia with 25G and 27G needles respectively developed PDPH. Difference was statistically insignificant. Conclusions: The incidence of PDPH was less in patients who underwent caesarean section under spinal anesthesia with 27G needle compared to that of patients in whom block was performed using 25G needles. However, there was no definite advantage of 27G Quincke needle over 25G Quincke needle as far as the incidence of PDPH is concerned.